Gravity Falls. Six strange tales - Aoshima, John; Pitt, Joe, (Director); Schaal, Kristen; Ritter, Jason, 1980-; Hirsch, Alex (Burbank, CA : Walt Disney Studios Home Entertainment, 2013)
Twelve-year-old twins Dipper and Mabel Pines spend the summer in mysterious Gravity Falls with their great uncle Stan, who runs a tacky tourist trap.
Tourist trapped -- The legend of the gobblewonker -- Headhunters -- The hand that rocks the Mabel -- The inconveniencing -- Dipper vs. manliness.
Dolby digital 2.0, wide screen 1.78:1.
Features: exclusive Mystery book : journal #3.
Voices: Kristen Schaal, Jason Ritter, Alex Hirsch, Linda Cardellini, Kevin Michael Richardson.
Originally broadcast on television in 2012.
TV rating: TV-Y7.
In English, French, or Spanish with optional French or Spanish subtitles.
Keywords: Twins -- Drama; Supernatural -- Drama; Summer -- Drama; Detective and mystery television programs; Television series; Fiction television programs; Video recordings for the hearing impaired; Comedy television programs; Animated television programs; Horror television programs; Detective television programs; Mystery television programs